2022
DOI: 10.1177/11206721221112150
|View full text |Cite
|
Sign up to set email alerts
|

The medication adherence among glaucoma patients during the coronavirus disease 2019 pandemic in Croatia

Abstract: Purpose This study aimed to evaluate the level of treatment adherence and identify predictors of adherence in glaucoma patients during the coronavirus disease 2019 (COVID-19) pandemic in Zagreb, Croatia. Methods The cross-sectional study was conducted among primary open-angle glaucoma (POAG) patients at the Department of Ophthalmology, University Hospital Centre Zagreb, between 1st April 2020 and 1st April 2021. The sociodemographic data, clinical, and drug information were recorded. The treatment adherence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…To effectively treat glaucoma, regular follow-ups, choice of treatment strategy, taking into account IOP, VF, and adherence, are necessary. Decreased adherence in patients with glaucoma due to the pandemic has been previously reported [9][10][11][12][13]. Adherence in this study was possibly lower, as in previous reports, for patients with worsened MD values.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…To effectively treat glaucoma, regular follow-ups, choice of treatment strategy, taking into account IOP, VF, and adherence, are necessary. Decreased adherence in patients with glaucoma due to the pandemic has been previously reported [9][10][11][12][13]. Adherence in this study was possibly lower, as in previous reports, for patients with worsened MD values.…”
Section: Resultssupporting
confidence: 79%
“…Japan approved a special measure allowing prescriptions to be sent remotely during the COVID-19 pandemic, allowing treatment continuation without running out of eye drops. However, patient adherence has reportedly worsened during that period [9][10][11][12][13]. This study aimed to retrospectively investigate the impact of hospital visit interruptions and the progression of visual eld impairment in patients with glaucoma, during the COVID-19 pandemic, using data from medical records.…”
Section: Introductionmentioning
confidence: 99%
“…Onwubiko et al [ 22 ] identified high rates of anxiety (44.0%) and depression (41.8%) among glaucoma patients in Enugu, Nigeria, with key contributing factors being reduced VA and also, blindness. Poor treatment adherence in glaucoma patients was associated with heightened anxiety, negatively affecting therapeutic outcomes[ 23 ]. According to the studies by Mabuchi et al [ 3 ] and Chen et al [ 4 ], the use of eye drops and the number of anti-glaucoma medications were not identified as significant risk factors for depression; furthermore, the use of topical β-blockers for glaucoma, showed no significant correlation with depression.…”
Section: Prevalence and Risk Factors Of Anxiety And Depression In Gla...mentioning
confidence: 99%
“…Non-adherence to treatment was prevalent among patients with POAG during the COVID-19 pandemic in various studies conducted on the different populations, including India ( 50 ), Croatia ( 51 ), United States ( 52 ), Egypt ( 53 ), and Pakistan ( 54 ). Before the pandemic, the main barriers to glaucoma medication adherence were cost, difficulty with drop instillation, and forgetfulness.…”
Section: Impact Of Covid-19 On Glaucoma Treatment Follow-up and Medic...mentioning
confidence: 99%